Whole exome sequencing identifies a novel mutation in Annexin A4 that is associated with recurrent spontaneous abortion - Ye, Qian; Liu, Fa-Ying; Xia, Xiao-Jian; Chen, Xiao-Yong; Zou, Li; Wu, Hui-Min; Li, Dan-Dan; Xia, Chen-Nian; Huang, Ting; Cui, Ying; Zou, Yang (Frontiers in Medicine, 2024)
Background: Recurrent spontaneous abortion (RSA) is a multifactorial disease, the exact causes of which are still unknown. Environmental, maternal, and genetic factors have been shown to contribute to this condition. The aim of this study was to investigate the presence of mutations in the ANXA4 gene in patients with RSA. Methods: Genomic DNA was extracted from 325 patients with RSA and 941 control women with a normal reproductive history for whole-exome sequencing (WES). The detected variants were annotated and filtered, and the pathogenicity of the variants was predicted through the SIFT online tool, functional enrichment analyses, Sanger sequencing validation, prediction of changes in protein structure, and evolutionary conservation analysis. Furthermore, plasmid construction, Western blotting, RT‒qPCR, and cell migration, invasion and adhesion assays were used to detect the effects of ANXA4 mutations on protein function. Results: An ANXA4 mutation (p.G8D) in 1 of the 325 samples from patients with RSA (RSA-219) was identified through WES. This mutation was not detected in 941 controls or included in public databases. Evolutionary conservation analysis revealed that the amino acid residue affected by the mutation (p.G8D) was highly conserved among 13 vertebrate species, and the SIFT program and structural modeling analysis predicted that this mutation was harmful. Furthermore, functional assays revealed that this mutation could inhibit cell migration, invasion and adhesion. Conclusion: Our study suggests that an unreported novel ANXA4 mutation (p.G8D) plays an important role in the pathogenesis of RSA and may contribute to the genetic diagnosis of RSA.